Experimental Study of Bifacial Solar Panels with Reflective Surface Variations in Bandung, Indonesia - Barokah, Rofi; Nia Nuraeni Suryaman; Ahmad Rajani (Universitas Muhammadiyah Sidoarjo, 2025)
This study aims to evaluate the performance of bifacial photovoltaic (PV) panels under different reflective surface conditions in a tropical urban environment, specifically in Bandung, Indonesia. Bifacial PV systems offer the advantage of capturing solar radiation from both the front and rear sides, with performance significantly influenced by the surface beneath the panels. The experiment involved three surface types: asphalt, untreated paving blocks, and paving blocks coated with white paint. Each panel was installed at a fixed 8° tilt facing north, and data were collected from 09:00 to 15:00 local time. The results indicate that the white-painted surface produced the highest power output, reaching up to 410 Watts, followed by paving blocks at 390 Watts and asphalt at 370 Watts. Although all surfaces received a similar radiation pattern, their differing reflectivity affected the amount of radiation reaching the rear side of the bifacial panels. The white-painted surface, characterized by high reflectance, not only enhanced rear-side radiation capture but also maintained a more stable power output after peak solar hours. These findings highlight the critical role of surface reflectivity in optimizing bifacial PV performance and support the strategic use of surface materials in PV system deployment, particularly in tropical climates. This study contributes valuable empirical data to the growing field of bifacial PV applications and offers practical insights for improving energy yield in real-world tropical settings.